PENGEMBANGAN WISATA AGRO: PELUANG KERJA MASYARAKAT DI KAWASAN PONCOKUSUMO KABUPATEN MALANG, PROVINSI JAWA TIMUR - NFN Triyono; Eniarti B. Djohan (Research Centre for Population, Indonesian Institute of Sciences, 2015)
This article aims to describe and assess the existence of This article aims to describe and assess the existence of agro-tourism in rural areas with regards to employment opportunities for local villagers around the area. This study used a socio culture approach by observing the supporting elements of tourism activities. This article derived from a research in Poncokusumo village, Malang District, of East Java Province, done in 2011. This village is currently developed as one of the Agropolitan Region in East Java Province including tourism, which expected to create job opportunities for people living around the area. This study used qualitative methods in the form of indepth interviews, observation and literature review.This study indicated that tourism, in particular agro tourism, has not been able to optimally provide employment opportunities for the local community. The problems, among others, were: 1 ) tourism activities are still run under conventional practices, 2) facilities and infrastructure needed to support tourism activities are inadequate, and 3) the absence of support from various stakeholders regarding tourism activity in Poncokusumo